Biobanking in oncology and radiology - Pavel O. Roumiantsev (Эндокринная хирургия, 2018)
The first biobank in Russia was created in 1998 to investigate post-Chernobyl thyroid tumors. The number of biobanks in the world is growing. Infrastructure and collaboration are improving. Ethical, legal and methodological guidelines for biobanking have been developed and are regularly reviewed. Biobanking objects are now not only biological samples of patients but also their dynamic biomedical characteristics. Comparison of genetics, proteome and tumour metabolism and in vivo radiological visualization is necessary to improve personalized diagnostics, treatment and its effectiveness. The article focuses on international evidence-based experience of sample preparation and cryopreservation of biological samples, information logistics, and integration solutions in biobanking. Guiding principles and the model of a modern biobank, integrating up-to-date technologies of digital personalized medicine and telemedicine in oncology and radiology are reported. The article may be of interest to a wide range of experts in biomedicine, especially oncologists, radiologists, pathologists, geneticists, and IT specialists.